Impaired plasmalogens in patients with schizophrenia - Kaddurah-Daouk, Rima; McEvoy, Joseph; Baillie, Rebecca; Zhu, Hongjie; K. Yao, Jeffrey; Nimgaonkar, Vishwajit L.; Buckley, Peter F.; Keshavan, Matcheri S.; Georgiades, Anastasia; Nasrallah, Henry A. (Psychiatry research, 2012)
Plasmalogens are a subclass of glycerophospholipids and ubiquitous constituents of cellular membranes and serum lipoproteins. Several neurological disorders show decreased level of plasmogens. An earlier study found differences in plasma phospholipids between unmedicated patients with schizophrenia and matched healthy control subjects. We here report a comparison of plasma plasmalogen levels across 20 drug-naïve patients experiencing first psychotic episodes, 20 recently unmedicated patients experiencing psychotic relapses after failing to comply with prescribed medications, and 17 matched healthy control subjects. Multiple plasma phosphatidylcholine and phosphatidylethanolamine plasmalogen levels were significantly lower in first episode patients and patients with recurrent disease compared to healthy controls. Reduced plasmalogen levels appear to be a trait evident at the onset of psychotic illness and after multiple psychotic relapses. It is implied that reductions in plasmalogen levels are not related to antipsychotic treatment but due to the illness itself. Reduced plasmalogen levels suggest impairments in membrane structure and function in patients with schizophrenia that might happen early in development. This may serve as a clue to the neurobiology of schizophrenia and should be studied as a potential biomarker for individuals at risk for schizophrenia.